Allele-specific transcription of the asthma-associated PHD finger protein 11 gene (PHF11) modulated by octamer-binding transcription factor 1 (Oct-1) - Holt, R; Zhang, Y; Binia, A; Dixon, A; Vandiedonck, C; Cookson, W; Knight, J; Moffatt, M (2011)
Background: Asthma is a common, chronic inflammatory airway disease of major public health importance with multiple genetic determinants. Previously, we found by positional cloning that PHD finger protein 11 (PHF11) on chromosome 13q14 modifies serum immunoglobulin E (IgE) concentrations and asthma susceptibility. No coding variants in PHF11 were identified. Objective: Here we investigate the 3 single nucleotide polymorphisms (SNPs) in this gene most significantly associated with total serum IgE levels - rs3765526, rs9526569, and rs1046295 - for a role in transcription factor binding. Methods: We used electrophoretic mobility shift assays to examine the effect of the 3 SNPs on transcription factor binding in 3 cell lines relevant to asthma pathogenesis. Relative preferential expression of alleles was investigated by using the allelotyping method. Results: Electrophoretic mobility shift assays show that rs1046295 modulates allele-specific binding by the octamer-binding transcription factor 1 (Oct-1). Analysis of the relative expression levels of the 2 alleles of this SNP in heterozygous individuals showed a modest, but highly significant (P = 6.5 × 10-16), preferential expression of the A allele consistent with a functional role for rs1046295. Conclusion: These results suggest a mechanism by which rs1046295 may act as a regulatory variant modulating transcription at this locus and altering asthma susceptibility. © 2010 American Academy of Allergy, Asthma and Immunology.